2015
DOI: 10.4236/jmp.2015.614217
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Physics in Diffusion Problems

Abstract: Using the divergence theorem and the coordinate transformation theory for the general Fickian second law, fundamental diffusion problems are investigated. As a result, the new findings are obtained as follows. The unified diffusion theory is reasonably established, including a self-diffusion theory and an N (N ≥ 2) elements system interdiffusion one. The Fickian first law is incomplete without a constant diffusion flux corresponding to the Brown motion in the localized space. The cause of Kirkendall effect and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Nevertheless, the problem of coordinate system of diffusion equation was not mathematically investigated in accordance with the divergence theorem in those days. The problems of the coordinate transformation relevant to the diffusion equation had not been thus discussed in the diffusion history for a long time before the previous work [4]. The new findings, which are extremely dominant in the diffusion study, were reasonably obtained through the coordinate transformation theory then.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Nevertheless, the problem of coordinate system of diffusion equation was not mathematically investigated in accordance with the divergence theorem in those days. The problems of the coordinate transformation relevant to the diffusion equation had not been thus discussed in the diffusion history for a long time before the previous work [4]. The new findings, which are extremely dominant in the diffusion study, were reasonably obtained through the coordinate transformation theory then.…”
mentioning
confidence: 59%
“…As is known from the unified theory of diffusion problems, the basic concept of diffusion phenomena is in the interdiffusion problems [4]. In the following discussion, the above raft model is reasonably applied to a typical binary system interdiffusion problem in accordance with the mathematical physics.…”
Section: Binary System Interdiffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…has been widely used for analyzing interdiffusion problems [6] [8] [9] [10] [11] [12], the equation itself is not only mathematically wrong in the derivation process but also entirely meaningless because of using the intrinsic diffusion coefficients nonexistent in the recent diffusion theory [7] [15]. In the present work, the physical meaning of K effect is reasonably discussed compared with experimental results, regardless of the Darken equation.…”
Section: Introductionmentioning
confidence: 89%
“…It is also physically considered that the diffusion region space interacts with the free space near the surface of specimen considered to be the sink and source [18]. This means that the coordinate transformation of the diffusion equation is necessary for analyzing interdiffusion problems [15] [16]. Using the solutions obtained here, the relation 3) Determination of initial and/or boundary values of diffusivities in a ternary system interdiffusion It is revealed that the so-called interdiffusion coefficient in a many elements system is meaningful only in the differential equation of diffusion [15] [18].…”
Section: Mathematical Theory Of Analytical Methodsmentioning
confidence: 99%